Asthma–COPD overlap syndrome among smoker subjects with asthma: A cross-sectional study - Safa Olimat, Shoroq M. Altawalbeh, Roqia S. Maabreh, Iman A. Basheti (Journal of Applied Pharmaceutical Science, 2024)
This study aimed to assess the prevalence of asthma–chronic obstructive pulmonary disease (COPD) overlap syndrome (ACOS) in asthmatic outpatients with smoking exposure (smokers or ex-smokers with ≥10 pack-year history) and to evaluate quality of life (QoL) and adherence among the study sample. This cross-sectional study was conducted at outpatient respiratory clinics in governmental hospitals in Jordan. Asthmatic outpatients were interviewed to assess their spirometric readings, patients’ adherence, and patients’ QoL [using the Mini Asthma QoL questionnaire (MiniAQLQ)]. The prevalence of ACOS was found to be 33% among asthmatic smoker patients in the outpatient setting (n = 65 out of 200 subjects with asthma-diagnosed patients recruited into the study). For subjects with ACOS, 47.7% of them were older than 60 years old. Smoking history for more than 30 years was prevalent among most subjects with ACOS (67.7%). The MiniAQLQ average score was found to be low (mean ± SD = 3.23 ± 1.01, score out of 7) and similarly for patients’ adherence to their treatment modalities (mean ±SD = 1.76 ± 1.2, score out of 6). A significant positive relationship between adherence to treatment and QoL was found among subjects with ACOS (correlation coefficient = 0.171, p-value = 0.018). In conclusion, a moderate prevalence of ACOS was estimated among asthmatic smoker patients. Low levels of QoL and adherence to treatment were significantly correlated.
Keywords: ACOS, quality of life, adult asthma adherence, asthma, COPD, smoking